AN ANALYSIS OF FACTORS CAUSING ANXIETY IN SPEAKING ENGLISH AT SMP NEGERI 2 BAUBAU - Syafitri, Nining; Amiruddin, Esa Penilta; Vinalia, Teani (English Education Department, 2023)
The problem statement of this researcher was whetherfactors causing anxiety in English Speaking on eighth-grade students at SMP Negeri 2 Baubau. The objective of the research was to find out the factors causing anxiety in English Speaking on eighth-grade students at SMP Negeri 2 Baubau. The design of this research was descriptive qualitative. The subjects of the research were seven students of Class VIII.1 at SMP Negeri 2 Baubau. The techniques of data collection in this study were observation and interview. Techniques of data analysis used were reduction of data, PresentationofData, and Verification The result showed that students experienced English speaking anxiety which consisted of internal factors and external factors. In internal factors, students' anxiety is a lack of confidence and fear of making mistakes. Meanwhile, on external factors, students experience anxiety, namely limited vocabulary and grammatical errors. Based on the result of the research, it was concluded that the most experienced by students is a lack of self-confidence.